The Role of Pickup Ions in the Interaction of the Solar Wind with the Local Interstellar Medium. II. Effects of Solar Cycle - R. K. Bera; F. Fraternale; N. V. Pogorelov; V. Roytershteyn; M. Gedalin; G. P. Zank (The Astrophysical Journal)
We investigate the role of pickup ions (PUIs) in the interaction of a periodically varying solar wind (SW) with the local interstellar medium (LISM). The analysis is performed using a 3D, time-dependent, multifluid model, where PUIs are treated as a separate fluid. The description of PUIs crossing the heliospheric termination shock utilizes results of kinetic simulations incorporated into magnetohydrodynamic (MHD) simulations. Space-time distributions of PUI properties throughout the heliosphere are presented. PUIs exhibit an intriguing behavior in the distant heliotail, where they are mostly concentrated in the vicinity of the heliopause (HP). Our simulations show that, because of the plasma mixing and MHD instabilities, PUIs created in the supersonic SW can cross the HP and enter the LISM. We find that the HP instability and solar cycle cause time-dependent variations in the flow of interstellar neutral atoms. When treated as a separate fluid, PUIs make the heliosphere slimmer, while the SW flow pattern in the heliotail exhibits enhanced variability. The simulation results are validated against in situ observations from the Voyager and New Horizons spacecraft.